Peptide Inhibitors of Angiotensin-I Converting Enzyme (ACE) Bioavailability in Legumes Subjected to Hydrothermal Treatment - Ojeda-Ojeda, Luis; Noguera-Machado, Nirza; López, José; Rivera, Valentina; Quintero, Héctor; Valero, Anira; Díaz, Joselyn; Pérez-Ybarra, Luis; Pacheco, Franklin (Indonesian Association of Food Technologists, 2024)
The objective of this study was to evaluate the effect of Angiotensin-I Converting Enzyme (ACE) inhibitory peptides derived from five legumes (Vigna unguiculata, Cicer arietinum, Lens culinaris, Vicia faba, and Phaseolus vulgaris) after undergoing a hydrothermal treatment. The seeds were divided into two groups: one was subjected to drying and grinding, and the other one to cooking for 2 hours (100 °C), followed by drying and grinding. The flours obtained from the different processes were subjected to digestion with pepsin-pancreatin, and the resulting peptides were evaluated for their ACE inhibitory activity. The obtained results were subjected to analysis of variance and Tukey's test. The group consisting of the treatments V. unguiculata (82.63%), V. unguiculata cooked (96.41%), and C. arietinum (80.84%) showed the highest percentages of ACE inhibition, while the group comprising V. faba (6.0%), cooked L. culinaris (3.03%), and P. vulgaris (4.0%) exhibited the lowest inhibition percentages. These results demonstrate that V. unguiculata, V. faba, and C. arietinum can undergo hydrothermal treatment while still retaining their bioactive potential, ensuring a cooked flour, ready for formulating a multifunctional food.